FEATURES OF SENSITIVITY TO ANTIBACTERIAL DRUGS IN PATIENTS WITH NONSPECIFIC SALPINGOOPHORITIS - Tertyshnyk, A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2016)
The features of microflora of the vagina in women patients with chronic nonspecific salpingoophoritis were studied, on the basis of which the main etiological factors of the disease, the features of the formation of associations of microorganisms which cause inflammation and the priorities for the adjustment of antimicrobial therapy were set. The investigations made indicate that in patients with chronic salpingoophoritis the changes of microflora of the vagina occur, accompanied by incoordination of its functioning as a single ecosystem, what is manifested by the disorders of microbiological status and widespread antibiotic resistance of the identified pathogens.